AAV2 serotype demonstrates the highest transduction efficiency in porcine lung-derived cells - Won Seok Ju; Seokho Kim; Areum Choi; Jae-Yeong Lee; Haesun Lee; Jingu No; Seunghoon Lee; Keonbong Oh; Jae Gyu Yoo (Journal of Animal Reproduction and Biotechnology)
Background: The ability of adeno-associated viruses (AAVs) to transduce various cell types with minimal immune responses renders them prominent vectors for gene editing (GE), with different AAV serotypes exhibiting distinct transduction efficiencies due to their specific cellular tropism. However, detailed molecular processes of AAV infection and penetration, as well as the optimal serotype for specific purposes, remain poorly understood. Porcine models are widely used in research benefitting both human and livestock due to anatomical and physiological similarities to humans. Methods: Transduction efficiencies of 18 AAV serotypes (AAV1–9, 6.2, rh10, DJ, DJ/8, PHP.eB, PHP.S, 2-retro, 2-QuadYF, and 2.7m8) were evaluated in immortalized porcine lung epithelial cells (pLCsImt) and pulmonary alveolar macrophages 3D4/31 (PAMs 3D4/31). Results: We found AAV2, DJ, and 2.7m8 to be the most effective in both cell types. The highest enhanced green fluorescent protein expression of 52.46 ± 2.4% in pLCsImt and 64.08 ± 2.4% in PAMs 3D4/31 was observed for AAV2, while negligible transduction was observed for AAV4, rh10, DJ, PHP.eB, PHP.S, and 2-retro. AAV-DJ showed superior transduction efficiency in PK-15, as compared to AAV2 and 2.7m8. Results emphasize the cell type-specific nature of AAV serotype transduction efficiencies. Notably, AAV2 was most effective in both lung and macrophage cells, whereas AAV-DJ was more effective in renal cells. Conclusions: Our findings suggest that AAV2 was identified as the most efficient serotype for transducing pLCsImt and PAMs 3D4/31, compare to the PK-15 cells. Understanding cell type-specific preferences of AAV serotypes offer crucial insight for tailoring AAV vectors to specific tissue and optimizing genome editing strategies, with potential implications for the advancement of personalized medicine and development of treatments for human and livestock.